Phenomoenology Study on Financial Performance and Management Accountability of Special Autonomy Funds Allocated for Education at the Province of Papua, Indonesia - Agustinus, John (Gadjah Mada International Journal of Business, 2013)
Special autonomy in education is regarded as a great blessing for the Papua people. They have high expectation that Special autonomy funds allocated for education will elevate their living quality including school provisions and living standard. The population of the research, however, perceived that such wishes and expectations did not match with the reality. It is assumed that there had been mismanagement of the funds. The study is aimed at reviewing special autonomy financial performance and its management accountability. The study is performed through a qualitative approach with a phenomenological strategyâ a study which is conducted at particular setting in a real live (natural setting) to investigate and understand phenomena. The data were collected from government employee, NGO officers, the target population, and other resources by observation, in-depth interviews, and library reviews. The results show that local government officials lack of capacity in handling the funds and there had been poor budget management as indicated from four management functions âplanning, executing, reporting, and monitoring of educational fundsâ which were not implemented appropriately. A concept as a set of law and regulation that shapes Special Autonomy fund management of Papua Province is needed. Therefore, an integrated mechanism of building compliance and control system of educational funds management is necessary to reach the Value for Money (effectiveness, efficiency, and economics) of education budget. It is recommended that knowledge building and understanding on the financial performance as mandated in Special Autonomy Article will strengthen the achievement of the target as stated in the vision, mission, and objectives which supported by a construct culture of transparency, frankness, accuracy, and accountability.